The feasibility of a coreless PCB isolation transformer in a low-profile low power DC-DC converter / Mohd Hafizhuzaimi Eleas - Eleas, Mohd Hafizhuzaimi (2007)
A low profile low power converter is in high demand especially for portable electronics application such as laptops and notebooks. The term low profile means low cost, low input voltage, low power and small in size.